Study on YB-laser welding applied on aluminum/polymer composites - Frank Reis, Jonas [UNESP]; Cintra, I. L.R. [UNESP]; Marques, L. F.B. [UNESP]; Ferrandini, P. L. [UNESP]; Abrahao, A. B.M.; Lima, M. S.F.; Botelho, E. C. [UNESP] (Taylor & Francis, 2024)
In the present study, an anodizing process was applied to aluminum alloy (AA2024-T3) to enhance interlocking in dissimilar joints with glass fiber-reinforced polyetherimide (GF/PEI) composite, using ytterbium-doped laser fiber welding as a heat source. A factorial Central Composite Design (CCD) was conducted to determine the most appropriate processing and optimization parameters, with lap shear strength (LSS) as the response variable. The obtained and fractured joints were characterized. Anodizing effectively improved the interlocking between dissimilar joints, resulting in LSS values of around 16 MPa. Surface impressions were observed in joints with lower shear values, likely due to the ineffective heat distribution in the processed joint. In the AA2024-T3 alloy, the annealing process occurred, beginning with the segregation of the alloy elements at the grain boundaries and subsequently reducing its hardness. The SEM analysis of the laminate in the best welding condition revealed a well-established fracture surface, with cusps, fibers covered by the polymer matrix, and river marks, indicating good consolidation of the process applied to the metal/polymer junction, which is consistent with the highest shear values obtained. These findings have important implications for future research and industrial applications and can help advance the understanding of these materials and processes.
Keywords: AA2024-T3 alloy; Anodizing; dissimilar joints; experiment planning; GF/PEI composite; ytterbium-doped laser fiber welding